Eu digital single market: measures against unjustified geo-blocking, electronic consumer contracts and the conflict of laws - Lafuente Sánchez, Raúl (CUADERNOS DE DERECHO TRANSNACIONAL, 2019)
The unjustified geo-blocking Regulation aims to eliminate direct and indirect discrimination based on customers’ nationality, place of residence or place of establishment. In order to achieve this goal, prohibits to traders the use of technological measures or otherwise, to block or limit a customer’s access to their online interfaces for reasons related to the customer’s nationality, place of residence or place of establishment. Moreover, the Regulation provides that compliance with its rules shall not be construed as implying that a trader directs activities to the Member State of the consumer’s habitual residence or domicile within the meaning of Brussels I Regulation and Rome I Regulation. This statement raises a possible interference with the criteria identified in the European Court of Justice case law, in order to delimit when a trader has directed his activities to the Member State of the consumer’s habitual residence or domicile. In this paper I analyze the aforementioned issue and its consequences for the electronic consumer contracts.
Keywords: EU digital single market; unjustified geo-blocking; regulation (EU) 2018/302; conflict of laws; electronic consumer contracts; concept of “directing activities”